Magnetic hydrogel for the rapid elimination of environmental harmful ions - Yoshihisa Namiki (Journal of Clinical Microbiology and Biochemical Technology - Peertechz Publications, 2020)
We have newly devised konjac glucomannan hydrogel pellets containing micrometer-sized iron particles and hydrotalcite powder [1], by which we can efficiently remove environmental harmful ions such as selenium, boron, fluorine and arsenic. Glucomannan hydrogel forms three-dimensional network which can stably immobilize these materials Figure 1. Iron Magnetic hydrogel (Japanese Patent 6667880 (2019)).